Late Quaternary Activity: Kouma Fault - He, Weimin; Wei, Leihua; Xu, Shuya; Wan, Senlin; Yang, Jie; Liu, Mingjun (Frontiers in Earth Science, 2022)
The Kouma Fault, located at the northern foot of the Mangshan Mountain in Luoyang City, Henan Province, China, is an active fault newly discovered in the field seismic geological survey. The Kouma Fault is a normal fault that is approximately 30 km in length, near the east-west strike, and the north dip. The study on the nature of the Quaternary activity of the Kouma Fault is of great significance to the potential seismic source zone division, urban and rural land planning, site selection for major projects, the assessment and prevention of earthquake disaster risk. Through a series of seismic geological surveys, 12 fault outcrops were discovered, which were all distributed on the slopes of the loess gullies. The Kouma Fault cuts loess, clay, sand, and gravel. The fault planes and scratch can be seen clearly. The filling in the fault zone is dominated by clay, loess, and pebbles, among others. When the width of the fault zone is smaller (10–30 cm), most clay in the zone is laminated in occurrence. The laminated surface is almost parallel to the fault plane and the long axis direction of pebbles in the fault zone is almost parallel to the fault plane. When the width of the fault zone is greater (for instance, 1.6 m), the clay and loess in the fault zone are massive. The composite drilling geological section and trench reveal 2 paleoseismic events of the Kouma Fault, the paleoseismic event I occurred at the fault in the Middle Pleistocene; the paleoseismic event II occurred at the fault in the later period of the Late Pleistocene, and the vertical offset of the upper Pleistocene bottom boundary is 13.57 m. Based on the OSL age data in the fault G1 outcrop of the fault and TC1 & TC2 trenches, the latest activity age of the Kouma Fault may be defined within the range of (38.84±4.69) to (40.90±4.45) kaB.P. The latest active age of the Kouma fault is the late of Late Pleistocene. The average vertical slip rate of the fault during the Late Pleistocene has been 0.11 mm/a.